A survey of UK general practitioners about depression, antidepressants and withdrawal: implementing the 2019 Public Health England report. (August 2020) - Read, John; Renton, Julia; Harrop, Christopher; Geekie, Jim; Dowrick, Christopher
Background: In 2019, a literature review indicated that more than half of people who try to come off antidepressants experience withdrawal effects. Both the National Institute of Health and Care Excellence and the Royal College of Psychiatrists updated their positions in line with that review, and Public Health England published a 152-page report called Dependence and withdrawal associated with some prescribed medicines: an evidence review . The report made several recommendations relevant to general practice. Method: In order to facilitate implementation of these recommendations, an online survey was designed to explore United Kingdom general practitioner (GP) experiences, opinions, knowledge and needs in relation to depression, ADs and withdrawal. A total of 66 GPs had completed the survey when COVID-19 occurred. Results: In keeping with previous findings, this small sample of GPs had a predominantly psycho-social perspective on the causes of, and treatments for, depression. They broadly considered ADs effective for moderate/severe depression and ineffective for minimal/mild depression, for which they preferred psychological therapies and social prescribing. There was a marked lack of consistency in GPs' knowledge about the incidence and duration of withdrawal effects. Only a minority (29%) felt their knowledge about withdrawal was 'adequate' and fewer (17%) believed this about their 'Ability to distinguish between withdrawal effects and return of the original problem (e.g. depression)'. Two-thirds (68%) would like more training on these matters. Conclusion: It is hoped that even this small sample will be helpful when designing, and seeking funding for, GP training programmes, and when implementing the PHE recommendations for support services, based in the primary care system, for the millions of people contemplating or initiating withdrawal from ADs every year in the UK.